Analisis Fenomena Hyperhonest Penggunaan Fitur Instagram Close Friends Dalam Batasan Privasi - Orvella Clara Chiquita; Poppy Febriana (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2023)
ABSTRACT With the development of new social media features that now make social media not only limited to exchanging information, but also used as a space for self-disclosure, one of which is self-disclosure on the Instagram "Close Friends" feature. With this feature, users can use it as a place to vent, express themselves more or be more honest by sharing private matters that are only known by the list of followers of their close friends. In terms of this phenomenon, it is called the hyperhonest phenomenon, namely venting more honestly. The purpose of the importance of this research is to find out and understand the hyperhonest phenomenon experienced by generation Z women in the Instagram close friends feature and the cyber culture of self-disclosure that is formed in the Instagram close friends feature, as well as to contribute to readers so that they consider disclosing personal information on the media. social. This study uses the study of Communication Privacy Management theory by Sandra Petronio (2002) which focuses on privacy management systems to regulate the level of privacy boundaries. The method used is Virtual Ethnography with in-depth interviews with 6 female respondents in the Z generation category and participant observation by researchers. The data validation technique uses data triangulation. Most of them set boundaries in sharing personal problems in the close friends feature that there is trust given to people they trust for shared information ownership, then cyber culture is formed in the Instagram close friends feature where the close friends space becomes a place of refuge to reveal personal information, share hyperhonest story.ABSTRAKDengan berkembangnya fitur – fitur baru media sosial yang kini membuat media sosial tidak hanya sebatas pertukaran informasi saja, namun digunakan juga sebagai ruang pengungkapan diri (self disclosure) salah satunya adalah pengungkapan diri pada fitur instagram “Close Friends”. Dengan fitur tersebut pengguna dapat memanfaatkannya sebagai tempat curhat mengungkapkan diri lebih banyak atau menjadi lebih jujur dengan membagikan hal privasi diri yang hanya diketahui oleh daftar pengikut close friends-nya saja. Dalam istilah fenomena tersebut disebut dengan fenomena hyperhonest, yaitu curhat lebih jujur. Tujuan dari pentingnya penelitian ini adalah Untuk mengetahui dan memahami fenomena hyperhonest yang dialami oleh generasi Z perempuan dalam fitur Instagram close friends serta budaya siber pengungkapan diri yang terbentuk di fitur Instagram close friends, serta memberikan kontribusi kepada pembaca agar mempertimbangkan dalam mengungkapkan diri informasi pribadi pada media sosial. Penelitian ini menggunakan kajian teori Manajemen Privasi Komunikasi oleh Sandra Petronio (2002) yang fokus pada sistem manajemen privasi untuk mengatur tingkat batas privasi. Metode yang digunakan adalah Etnografi Virtual dengan wawancara mendalam dengan 6 responden perempuan kategori generasi Z dan observasi partisipan oleh peneliti. Teknik keabsahan data menggunakan Triangulasi data. Sebagian besar mereka mengatur batasan dalam berbagi masalah pribadi di fitur close friends bahwa adanya kepercayaan yang diberikan terhadap orang yang dipercayainya untuk kepemilikan informasi bersama, lalu budaya siber yang terbentuk dalam fitur Instagram close friends dimana ruang close friends menjadi tempat berlindung mengungkapkan diri informasi pribadi, membagikan curhatan lebih jujur.